Spontaneously Regenerative Tough Hydrogels. (1st July 2019) - Qu, Gang; Li, Yang; Yu, Yafeng; Huang, Yuxing; Zhang, Wei; Zhang, Han; Liu, Zhou; Kong, Tiantian
Abstract: Sponges, Neofibularia nolitangere, can regenerate spontaneously after being broken down into small pieces, and the regenerated structure maintains the original appearance and function. Synthetic materials with such capabilities are highly desired but hardly achieved. Presented here is a sponge‐inspired self‐regenerative powder from a double‐network (DN) tough hydrogel. Hydrogels are regenerated from their powder form, by addition of water, with preservation of the original appearance and mechanical properties. The powder‐hydrogel‐powder cycle can be repeated multiple times with little loss in mechanical properties, analogous to the regeneration of sponges. These DN hydrogels can be conveniently stored and easily shaped upon regeneration. This work may have implications in the development of regenerative materials for coatings and adhesives. Abstract : Selbstheilung : Ein selbstregenerierendes Doppelnetzwerk‐Hydrogel wurde entwickelt, das sich spontan aus seiner trockenen Pulverform regenerieren kann. Die Pulver können zu Hydrogelen mit dem ursprünglichen Aussehen und der Superdehnbarkeit zurückgeführt werden. Die Pulver‐zu‐Hydrogel‐Transformation bietet beispiellosen Komfort sowohl für die Lagerung als auch für die Formgebung zäher Materialien auf Hydrogelbasis.